Large Vessel Arteriopathy After Cranial Radiation Therapy in Pediatric Brain Tumor Survivors. (April 2018) - Nordstrom, Matthew; Felton, Erin; Sear, Katherine; Tamrazi, Benita; Torkildson, Joseph; Gauvain, Karen; Haas-Kogan, Daphne A.; Chen, Josephine; Buono, Benedict Del; Banerjee, Anuradha; Samuel, David; Saloner, David; et al.
Among childhood cancer survivors, increased stroke risk after cranial radiation therapy may be caused by radiation-induced arteriopathy, but limited data exist to support this hypothesis. Herein, we assess the timing and presence of cerebral arteriopathy identified by magnetic resonance angiography (MRA) after cranial radiation therapy in childhood brain tumor survivors. In a cohort of 115 pediatric brain tumor survivors, we performed chart abstraction and prospective annual follow-up to assess the presence of large vessel cerebral arteriopathy by MRA. We identified 10 patients with cerebral arteriopathy. The cumulative incidence of arteriopathy 5 years post–cranial radiation therapy was 5.4% (CI 0.6%-10%) and 10 years was 16% (CI 4.6%-26%). One patient had an arterial ischemic stroke 2.4 years post–cranial radiation therapy in the distribution of a radiation-induced stenotic artery. We conclude that large vessel arteriopathies can occur within a few years of cranial radiation therapy and can become apparent on MRA in under a year.